The value of quantitative histology in the diagnosis of fracture-related infection. (July 2018) - Morgenstern, M.; Athanasou, N. A.; Ferguson, J. Y.; Metsemakers, W-J.; Atkins, B. L.; McNally, M. A.
Abstract : Aims: This study aimed to investigate the role of quantitative histological analysis in the diagnosis of fracture-related infection (FRI). Patients and Methods: The clinical features, microbiology culture results, and histological analysis in 156 surgically treated nonunions were used to stratify the likelihood of associated infection. There were 64 confirmed infected nonunions (one or more confirmatory criteria: pus, sinus, and bacterial growth in two or more samples), 66 aseptic nonunions (no confirmatory criteria), and 26 possibly infected nonunions (pathogen identified from a single specimen and no confirmatory criteria). The histological inflammatory response was assessed by average neutrophil polymorph (NPs) counts per high-power field (HPF) and compared with the established diagnosis. Results: Assuming a cut-off of over five neutrophils per high-power field to diagnose septic nonunion, there was 80% sensitivity and 100% specificity (accuracy 90%). Using a cut-off of no neutrophils seen in any high-power field to diagnose aseptic nonunion, there was a sensitivity of 85% and a specificity of 98% (accuracy 92%). Conclusion: Histology can be used in a bimodal fashion as a diagnostic test for FRI. The presence of more than five NPs/HPF had a positive predictive value for infected nonunion of 100%, while the complete absence of any NPs is almost always indicative of an aseptic nonunion (positive predictive value of 98%). Cite this article: Bone Joint J 2018;100-B:966–72.